Recent advances in drug delivery technology - Keservani, Raj K., 1981-; Sharma, Anil K., 1980-; Kesharwani, Rajesh Kumar, 1978- (Advances in Medical Technologies and Clinical Practice (AMTCP) book Series, 2017)
"[This book] is a pivotal reference source for the latest scholarly research on the application of pharmaceutical technology to optimize techniques for drug delivery in patients"--Provided by publisher.